Alterations in the epidermis of the carp, Labeo rohita (Cyprinidae: Cypriniformes), infected by the bacteria, Aeromonas hydrophila: A scanning electron microscopic, histopathological and immunohistochemical investigation. Issue 8 (2nd July 2020) - Srivastava, Ayan; Mistri, Arup; Mittal, Swati; Mittal, Ajay Kumar
Abstract: This study was carried out to comprehend the pathogenicity of the bacteria in the epidermis of Labeo rohita inoculated with Aeromonas hydrophila . Alterations in the histopathology of the epidermis were examined using scanning electron microscopy, light microscopy and the localization of iNOS and caspase 3 + ve cells by means of immunohistochemical methods. Skin samples obtained from infected fish at different intervals 2, 4, 6, 8 and 10 days showed significant changes in the cellular components of the epidermis. Epithelial cells often appeared hypertrophied with fragmented and loosely arranged microridges, and in the process of exfoliation. Mucous goblet cells increased significantly in density. Club cells showed degenerative changes, often with simultaneous confluence of adjacent cells and release of their contents. Increase in density of iNOS and caspase 3 + ve cells indicates inflammatory response and apoptosis. This study could provide valuable information on the pathogenesis of the disease, and disease outbreaks in farmed fish. Further, it could provide useful guidelines for fish farmers to take preventive measures for the control of the disease.